2008
DOI: 10.2174/157015908785777210
|View full text |Cite
|
Sign up to set email alerts
|

Brain Endothelial Cell-Cell Junctions: How to “Open” the Blood Brain Barrier

Abstract: The blood-brain barrier (BBB) is a highly specialized structural and biochemical barrier that regulates the entry of blood-borne molecules into brain, and preserves ionic homeostasis within the brain microenvironment. BBB properties are primarily determined by junctional complexes between the cerebral endothelial cells. These complexes are comprised of tight and adherens junctions. Such restrictive angioarchitecture at the BBB reduces paracellular diffusion, while minimal vesicle transport activity in brain en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
378
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(396 citation statements)
references
References 183 publications
5
378
0
1
Order By: Relevance
“…Despite this, infiltration of circulating cells has been shown to occur when BBB permeability is increased. Thus T cell infiltration has been found in CNS tissues of patients with Parkinson's disease (Stone et al, 2009) and Alzheimer's disease (Schindowski et al, 2007;Togo et al, 2002) and infiltration of cells has also been reported following ischemic insult and with age (Popescu et al, 2009) and bacterial and viral infections (Stamatovic et al, 2008). In this study, increased BBB permeability was associated with increased expression of IP-10 and MCP-1.…”
Section: Discussionsupporting
confidence: 59%
“…Despite this, infiltration of circulating cells has been shown to occur when BBB permeability is increased. Thus T cell infiltration has been found in CNS tissues of patients with Parkinson's disease (Stone et al, 2009) and Alzheimer's disease (Schindowski et al, 2007;Togo et al, 2002) and infiltration of cells has also been reported following ischemic insult and with age (Popescu et al, 2009) and bacterial and viral infections (Stamatovic et al, 2008). In this study, increased BBB permeability was associated with increased expression of IP-10 and MCP-1.…”
Section: Discussionsupporting
confidence: 59%
“…These events are followed by relatively small increases of T and B lymphocytes. Strokeinduced disruption of the blood-brain barrier (BBB) facilitates the migration of immune cells into the brain [29][30][31]. Circulating monocytes gain access to brain parenchyma via endothelial migration and differentiate into tissue macrophages.…”
Section: Impact Of Stroke On Immunitymentioning
confidence: 99%
“…VVO on the other hand are large collection of interconnected vesicles and vacuoles. The fusion of vesicles, vacuole with luminal and abluminal plasma membranes creates transcellular pathways confirmed in the several ultrastructural studies (Stamatovic et al, 2008).…”
Section: Blood-brain Barrier: Structure and Functionmentioning
confidence: 61%
“…The impediment to ion movement results in the high in vivo electrical resistance of the BBB, of 1800 Ω cm 2 . This high electrical resistance or low conductance of the potential paracellular pathway emphasises the extreme effectiveness of the TJs in occluding this pathway by effectively reducing the movement of ions (Abbott et al, 2010;Paolinelli et al, 2011;Stamatovic et al, 2008). However, the BBB is a dynamic structure capable of rapid modulation in response to physiological or pathological signals.…”
Section: Blood-brain Barrier: Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation